A framework for understanding the different research avenues of living labs. (2016) - Leminen, Seppo; Westerlund, Mika
This study identifies eight prevailing research avenues of living labs, an increasingly popular innovation approach, based on a comprehensive literature review. So doing, the study contributes to the literature of living labs by discussing perspectives that scholars in the field have taken to understand living labs and by providing an integrative framework to position these perspectives as distinct research avenues. Moreover, the study shows that the identified avenues share the view of living labs as real-life environments and recognise the crucial role of users in innovation.